Validity and reliability of the PictorialPediatric Symptom Checklist - (:unkn) unknown (My University, 2020)
Objectives: This study was conducted methodologically to adapt the Pictorial Pediatric Symptom Checklist (PPSC)into Turkish and test its validity and reliability. The adaptation of the PPSC into Turkish will ensure the early diagnosis atrisk children aged 6–16, directing families and children to necessary health institutions in a timely manner for detaileddiagnosis and treatment; it shall also mean that nationwide studies can be conducted at a lower cost, as well as moreeffectively and more easily.Methods: This methodological study was completed using 799 parents whose children, aged 6–16 years, were studying in two different primary schools in Istanbul.Results: Content and construct validity were used to validate the PPSC, while internal consistency and test-invariancetechnique were used for reliability. The Content Validity Index was found to be 92.2%. Within the item-total correlations,only one item’s correlation (item 20) was found to be below 0.30 and it was removed from the scale. Thus, the factoranalysis of the scale was applied to a total of 34 items. A four-factor structure emerged as a result of the factor analysisand the factor loadings of the items were found to be between 0.33 and 0.72. The total variance of the four-factor structure is 37.63%. The Cronbach alpha value of the PPSC was calculated as 0.89.Conclusion: The Turkish version of the PPSC was found to be a valid and reliable surveying tool that provides the opportunity to examine children’ psychosocial and behavioral problems.